Enhancing Government Accountability through Responsibility Accounting: A Systematic Literature Review - Mediaty Mediaty; Asri Usman; Muh. Silmi Kaffah Yusuf; Khairum Nadila Sandy (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Responsibility accounting plays a key role in enhancing government accountability, especially in the management of public funds. This study aims to explore the implementation of responsibility accounting in the public sector and identify the mechanisms and challenges involved in enhancing accountability in government institutions. Through a systematic literature review, this study identifies that clear budget allocation, transparent financial reporting, and effective auditing are key mechanisms that support government accountability. However, significant challenges, such as inconsistencies in budget allocation, data limitations, and lack of adequate technological infrastructure, hinder the optimal implementation of responsibility accounting. Additionally, information technology and data-driven management systems play a crucial role in enhancing the effectiveness of budget oversight and preventing the misuse of public funds. Overall, although responsibility accounting has excellent potential, existing challenges need to be addressed through capacity and infrastructure development, as well as policy reforms, to achieve a more efficient and transparent accounting system in the public sector.